Are there oil currencies? The real exchange rate of oil exporting countries - Maurizio Michael Habib; Margarita Manolova Kalamova (European Central Bank (ECB), 2007)
This paper investigates whether the real oil price has an impact on the real exchange rates of three main oil-exporting countries: Norway, Russia and Saudi Arabia. We create our measure of the real effective exchange rates for Norway and Saudi Arabia (1980-2006) and for Russia (1995-2006), testing if real oil prices and productivity differentials against 15 OECD countries influence exchange rates. In the case of Russia it is possible to establish a positive long-run relationship between the real oil price and the real exchange rate. However, we find virtually no impact of the real oil price on the real exchange rates of Norway and Saudi Arabia. The diverse exchange rate regimes cannot help in explaining the different empirical results on the impact of oil prices across countries, which instead may be due to other policy responses, namely the accumulation of net foreign assets and their sterilisation, and specific institutional characteristics.
Keywords: F31; C22; 330; oil exporting countries; Oil Price; purchasing power parity; real exchange rate; terms of trade; Ölpreis; Kaufkraftparität; Terms of Trade; Norwegen; Russland; Saudi-Arabien; OECD-Staaten